Latency-associated Peptide Identifies Immunoevasive Subtype Gastric Cancer With Poor Prognosis and Inferior Chemotherapeutic Responsiveness. Issue 1 (January 2022) - Cao, Yifan; He, Hongyong; Li, Ruochen; Liu, Xin; Chen, Yifan; Qi, Yangyang; Yu, Kuan; Wang, Jieti; Lin, Chao; Liu, Hao; Zhang, Heng; Li, He; et al.
Abstract : Objective: To examine the clinical significance of LAP to predict survival outcomes and chemotherapeutic responsiveness in gastric cancer. Background: LAP has been shown to possess significant immunoregulatory roles in several malignancies. However, the role and clinical significance of LAP in gastric cancer still remains unknown. Methods: Four hundred and fifty-six tumor tissue microarray specimens, 80 fresh tumor tissue samples of gastric cancer patients from Zhongshan Hospital, Fudan University and transcriptomic and clinical data of 328 gastric cancer patients from the Cancer Genome Atlas were analyzed. LAP expression and immune contexture were examined by immunohistochemistry, CIBERSORT, and flow cytometry. Clinical outcomes of patient subgroups were compared by Kaplan-Meier curves, Cox model and interaction test. Results: High LAP expression predicted poor overall survival ( P < 0.001, P < 0.001, and P = 0.022) and inferior therapeutic responsiveness to fluorouracil-based adjuvant chemotherapy ( P = 0.008 for interaction) in gastric cancer. LAP was associated with immunoevasive tumor microenvironment featured by dysfunctional CD8 + T cells infiltration ( P < 0.001). The LAP-associated dysfunctional CD8 + T cells had an exhausted phenotype with decreased effector molecules such as interferon-γ, granzyme B, and perforin, but also elevated programmed cell death protein-1, which resulted in poor prognosis and inferior therapeutic responsiveness. Conclusions: This study revealed that LAP could identify immunoevasive subtype gastric cancer, indicating LAP might be a potential immunotherapeutic target and facilitate patient counseling on individualized adjuvant therapy and follow-up scheduling in gastric cancer. Abstract : Supplemental Digital Content is available in the text